Mathematical sciences, technology, and economic competitiveness - Glimm, James; Griffiths, Phillip, 1938-; National Research Council (U.S.). Board on Mathematical Sciences; National Research Council (U.S.). Commission on Physical Sciences, Mathematics, and Applications (Washington, D.C. : National Academy Press, 1991)
This book describes the contributions of mathematics to the nation's advanced technology and to economic competitiveness. Examples from five industries--aircraft, petroleum, automotive, semiconductor, and telecommunications--illustrate how mathematics enters into and improves industry. Mathematical Sciences, Technology, and Economic Competitiveness addresses these high-technology industries and breadth of mathematical endeavors in the United States as they materially contribute to the technology base from which innovation in these industries flows. The book represents a serious attempt by the mathematics community to bring about an awareness by policymakers of the pervasive influence of mathematics in everyday life.
Key American Industries -- Aircraft -- Semiconductors and Computers -- Petroleum -- Automobiles -- Telecommunications -- The Product Cycle -- Economic Planning -- Simulation and Design: Aircraft -- Design and Control of Complex Systems -- Machine Tools for Manufacturing -- Simulation and Production: Petroleum -- Statistical Quality Control and Improvement -- Manufacturing Process Control -- Sensor-Based Manufacturing -- Manufacturing Standards -- Production, Inventories, and Marketing -- Maintenance and Repair -- The Technology Base -- Technology Transfer -- Simulation and Computational Modeling -- Statistical Quality Improvement -- Differential Equations -- Optimization, Discrete, and Combinatorial Mathematics -- Statistical and Probabilistic Models -- Manpower, Education, and Training -- Findings and Recommendations.
Board chairman: Phillip A. Griffiths.
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Mathematics -- Study and teaching; Mathematics -- Research; Technology transfer; Competition, International; Technology Transfer; Mathématiques -- Étude et enseignement; Transfert de technologie; Concurrence internationale; MATHEMATICS -- Pre-Calculus.; MATHEMATICS -- Reference; MATHEMATICS -- Essays; Competition, International; Mathematics -- Research; Mathematics -- Study and teaching; Technology transfer